New species of Alpinalona Alonso & Sinev, 2017 (Cladocera: Anomopoda: Chydoridae) from South-East USA - Sinev, Artem Y. (Zootaxa, 2020)
A new species of genus Alpinalona Alonso & Sinev, 2017 is described from South-East USA. Alpinalona fornshelli sp. nov. differs from other species of the genus in: (1) over 35 setulae on posteroventral angle of the valves, organized into 5–6 groups; (2) a long basal spine of female postabdominal claw (about 0.3 claw length); and (3) thick long distalmost spines in basal pecten of postabdominal claw. Taxonomic position and distribution of the new species are discussed.